Banking Company Value Through Company Size, Growth Assets and Profitability - Amin, Asbi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to test the influence of company size,growth assetsand profitability on company value.This type of research is quantitative research. The population used in this study are all banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period taken from its official website totaling 40. The sample used in this study is banking companies listed on the Indonesia Stock Exchange (IDX). according to the sample selection criteria up to 34. The data collection technique used in this study is documentary research by collecting and studying documents related to the research obtained from the Indonesia Stock Exchange (IDX) or other websites (www.idx.co.id and the company website). financial reports (annual reports) that have been published by the company. This study uses descriptive statistical analysis and multiple linear regression analysis. The results of the study found that company size and asset growth did not have a significant effect on company value, while profitability had a significant effect on company value.